Experimental Investigation of Neutralisation of Concrete with Fly Ash as Fine Aggregate in Freeze-Thaw Environment. (25th June 2019) - Zhang, Dongsheng; Mao, Mingjie; Yang, Qiuning; Zhang, Wenbo; Han, Pengfei
Abstract : To study the durability of concrete with fly ash as fine aggregate under alternate freeze-thaw and carbonation, freeze-thaw and carbonation cyclic tests are conducted to explore variation characteristics such as relative dynamic modulus of elasticity and neutralisation depth. The influence coefficient ( λ C ) of carbonation on concrete freeze-thaw damage and the influence coefficient ( λ F ) of freeze-thaw on concrete neutralisation are introduced. In addition, scanning electron microscopy is performed to reveal the deterioration mechanism of the alternating effect. Finally, through a regression analysis of test data, the mathematical expression of the composite damage coefficient k F under alternate freeze-thaw and carbonation is obtained. Based on these findings, a prediction model of the neutralisation depth of concrete is established with number of freeze-thaw cycles and water-cement ratio as parameters. The values calculated through this model and the values measured in the tests are highly correlated. This provides a theoretical reference and basis for the analysis of concrete durability in a multifactor environment.